Monitoring and Assessment of Human Health and Medical Care in Ukraine - V. V, Chorna; V. M., Makhniuk; S.S., Khliestova; N.I., Gumeniuk (International Journal of Scientific Research and Management (IJSRM), 2021)
The article an assessment of the integrated index of health and medical care of the population of the European Union and the population of other countries according to the UN (2019) and a description of the main factors that affect this indicator. Theoretical and practical analysis of the definition of the integrated index of health and medical care of doctors, nurses and beds of Ukraine in 2010, 2017 years. We have been developing a methodology for calculating the human health index (HDI) based on mortality, disability, and morbidity indicators for an objective assessment of the health status of the population of Ukraine.